Acute effect of breaking up prolonged sitting on cognition: a systematic review. Issue 3 (15th March 2022) - Chueh, Ting-Yu; Chen, Yung-Chih; Hung, Tsung-Min
Abstract : Objectives: To review the current evidence on the acute effects of interrupting prolonged periods of sitting with intermittent physical activity (PA) on cognition in healthy populations. Design: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Methods: Studies were included if they investigated the acute effects of taking regular PA breaks from sitting on cognition in healthy populations without any cardiovascular disease, history of brain injury, or psychiatric or neurological disorder. Four electronic databases—PubMed, Scopus, MEDLINE and ProQuest—were searched for eligible studies on 20 September 2020. Study quality was assessed using the Physiotherapy Evidence Database scale. Results: Seven studies, involving 168 participants aged between 18 and 80 years, were eligible for inclusion in this review. Three of the seven studies found positive effects of interrupting sitting with either (a) 3 min of relatively high-intensity (6 km/hour) walking every 30 min on attention and inhibitory control in young adults; (b) hourly breaks with progressively longer duration (10–30 min) of very light-intensity cycling/walking on attention, working memory and cognitive flexibility in adults with obesity; or (c) an initial bout of continuous moderate-intensity exercise, followed by interruption of post-exercise sitting with 3 min breaks of light-intensity walking (3.2 km/hour) every 30 min, on working memory in older adults with overweight. Conclusion: Given the limited evidence with mixed findings on this topic in the literature and the heterogeneity of PA protocols across the included studies, the results regarding the effectiveness of interrupting prolonged sitting with PA breaks in improving cognition warrant further verification. PROSPERO registration number: CRD42020147536.